The relationship of Islamic Religious Education Teachers’ Pedagogical Competence with Independent Curriculum Learning Achievement and Learning Outcomes in the Aqidah Akhak Subject - Azaz Abdul Muharom; Joko Subando (Universitas Muhammadiyah Enrekang, 2024)
The education system has an important role in influencing the growth of a country, especially in developing human resources. The curriculum is one of the main components of education, which is designed to create a conducive learning environment and support the achievement of learning outcomes. In Indonesia, the curriculum is regularly updated to adapt to current developments and maintain the relevance of education. This research aims to analyze the relationship between the pedagogical competence of Islamic Religious Education (PAI) teachers regarding the learning outcomes of the Merdeka Curriculum and the learning outcomes of the Aqidah Akhlak subject. The research was conducted in Sragen, with a population of 165 class VIII students, and a sample of 66 students from class VIII A and B who were selected using a purposive sampling technique. Data was collected through questionnaires to measure students' perceptions of teachers' pedagogical competence and learning outcomes. The research results show that teachers' pedagogical competence is in the medium category, with details of 23.8% low, 59% medium and 15.2% high. Students' Aqidah Moral learning outcomes are also in the medium category, with 20% low, 65% medium, and 15% high. Correlation analysis shows that there is a significant relationship between teacher pedagogical competence and Aqidah Akhlak learning outcomes, with Sig. (2-tailed) of 0.434 for teacher pedagogical competence and 0.00 for learning outcomes, both <0.05. This research provides evidence of a positive correlation between teacher pedagogical competence and student learning outcomes, as well as providing recommendations for improving the quality of learning